Phytogenic CeO2-Sm2O3 nanocomposites with enhanced catalytic activity for reduction of 4-nitrophenol. (12th June 2019) - Pinheiro, Dephan; Devi, K R Sunaja; Karthik, K; Jose, Ajay; Sugunan, Sankaran
Abstract: The phytogenic synthesized CeO2 -Sm2 O3 is a green, efficient and cost-effective catalyst. The CeO2 -Sm2 O3 composite was characterized using XRD, FTIR, Raman, TGA, UV-DRS, TEM, FE-SEM and EDAX. The synthesized CeO2 -Sm2 O3 shows a high catalytic activity for the reduction of 4-nitrophenol in the presence of the sodium borohydride under ambient conditions. This CeO2 -Sm2 O3 nanocomposite catalyst shows good stability and reusability without much loss in conversion efficiency. CeO2 -Sm2 O3 possess great prospects in the reduction of nitro organic pollutants in water.